HUBUNGAN POLA ASUH ORANG TUA DENGAN TINGKAT PERKEMBANGAN ANAK USIA 4-6 TAHUN DI RW 01 PERMATA BALARAJA KABUPATEN TANGERANG - Listiani, Alissa Dwi; Nuryanti (Nusantara Hasana Berdikari, 2021)
The development experienced by a child is a series of regular changes from one stage to another. Development to the next stage of overall development. Parents are tools for children to adapt to the environment, understand the world around them and the general pattern of social life in that environment. This is because parents are the first basis for the formation of children's character. The formation of parenting patterns is closely related to the personality of children as adults. Objective: To determine the relationship between parenting styles and the level of development of children aged 4-6 years. Method: The sampling technique used in this study was purposive sampling. The research sample from the community who attended was 105 respondents. Results: chi-square test results The relationship between parenting patterns and prevention of the level of development of children aged 4-6 years p-value = 0.011 < 0.05 means that there isignificant relationship between parenting patterns and the level of development of children aged 4-6 year. Conclusions and suggestions: The results of the study there is significant relationship between parenting patterns with the level of development of children aged 4-6 years. It is hoped that parents can find out more about the development of children aged 4-6 years so that they can provide the right stimulus in every stage of the child's development.